Accessing Assessment: The Correspondence of Longitudinal Assessment Tools to Grades in a Writing-Intensive Course - Christopher Roland; Jessica Welch; Joshua Boyd (Journal of the Scholarship of Teaching and Learning)
Researchers have long cast grades as an unreliable proxy for student learning despite their enduring use in higher education. Grounding assessment instruments in student learning outcomes (SLOs) provides an accurate and accessible means of evaluating student performance and guiding instructional practice. Using a SLO-guided pre-test/post-test assessment instrument, this study evaluated the correspondence between student learning and grades in a writing-intensive, large-lecture communication course. Learning scores were found to be significantly positively associated with final grades and scores on individual assignments. The study further explored differences in learning and grades between online and in-person course formats. Implications for assessment instrument design are discussed.